Temperature sensor with anisotropic structure, and preparation method and application thereof

By using the gradient distribution of gallium-based alloy liquid metal in the temperature sensor and working in a coordinated manner, the accuracy and response speed of existing temperature sensors under extreme temperature conditions are solved, and efficient and low-cost temperature monitoring is achieved. in the fields of industry and medical care.

CN119268867APending Publication Date: 2025-01-07SHIJIAZHUANG TIEDAO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410541583.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing temperature sensors have low accuracy, slow response speed, insufficient sensitivity and high cost under extreme temperature conditions, which limit their wide application in industries and medical fields.

Method used

Using a temperature sensor with an anisotropic structure, by injecting gallium-based alloy liquid metal into the hollow fibers, a gradient-distributed liquid metal oxide layer works in concert with the thermoresistance effect, thereby improving the response speed and accuracy of the sensor.

Benefits of technology

High linearity in the range of 20°C to 80°C and fast response time of 10 seconds are achieved, reducing costs, improving sensor resolution and response time, and enhancing sensor stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004821141350000081
    Figure BDA0004821141350000081
  • Figure BDA0004821141350000082
    Figure BDA0004821141350000082
  • Figure BDA0004821141350000083
    Figure BDA0004821141350000083
Patent Text Reader

Abstract

The invention provides a temperature sensor with an anisotropic structure, and a preparation method and application thereof. The temperature sensor with the anisotropic structure structurally comprises a hollow fiber, liquid metal distributed in a gradient mode is formed in the hollow fiber through injection, and the two ends of the hollow fiber are coated with conductive silver paste. The flexible temperature sensor based on the liquid metal is developed by accurately controlling the injection speed of the flexible temperature sensor to the inner wall of the hollow fiber with the coarse structure. The liquid metal not only shows a thermal resistance effect in the hollow fiber, but also deforms due to increase of gas pressure, which is a synergistic effect of thermal resistance and strain of the liquid metal, so that the resolution of the sensor is enhanced. The temperature sensor provided by the invention realizes high linearity and quick response time of 10 seconds in a range of 20 DEG C to 80 DEG C, and provides a reliable way for further improving the resolution and the response time of the temperature sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of temperature sensors, in particular to a temperature sensor with an anisotropic structure, a preparation method and application thereof. Background Art

[0002] As an important device for measuring ambient temperature, temperature sensors play a key role in science, industry, and medical fields. In industrial production, they are used to monitor and control temperature changes in various production processes, such as metal processing, chemical reactions, and heat treatment processes. In environmental monitoring, temperature sensors are used in weather stations, greenhouses, and ecosystem monitoring so that timely measures can be taken to address climate change. In the field of healthcare, temperature sensors are used in medical devices such as thermometers and temperature controllers to monitor patient temperature changes and adjust the operating temperature of medical equipment. In addition, engine temperature sensors and in-car temperature sensors in the automotive industry, as well as temperature sensors in appliances such as ovens, refrigerators, and washing machines in home appliances, are all common application scenarios. In general, the application range of temperature sensors is very wide, covering all aspects of life, and they play an important role in improving production efficiency, improving the quality of life, and protecting people's health and safety.

[0003] Common temperature sensors include thermistors, thermocouples, and infrared sensors, each of which has its own specific working principle and application range. However, these sensors have more or less some defects and shortcomings, which limit their application in some specific scenarios.

[0004] First, some temperature sensors have the problem of low accuracy. Especially under extreme temperature conditions, the accuracy of some sensors may be affected, resulting in insufficient accuracy of measurement results. This may affect the accurate monitoring and control of temperature changes, especially in applications with high temperature requirements, such as industrial production and medical equipment. Secondly, some sensors in the prior art have a slow response speed and cannot reflect temperature changes in real time. In some application scenarios that require a quick response, this delay may cause problems or safety hazards, such as when the temperature suddenly rises or drops and immediate measures need to be taken to control or adjust the environment. In addition, some sensors are not sensitive enough to accurately capture small temperature changes. In fields that are more sensitive to temperature changes, such as scientific research and laboratory applications, this may affect the accuracy and repeatability of experimental results. Cost is also a factor that affects the application of some sensors. Some high-precision, high-performance temperature sensors are expensive and are not suitable for large-scale applications or projects with limited budgets. This makes it possible for some fields to not be able to afford the high equipment costs, thereby limiting the popularity and application of sensors. Finally, some sensors may have stability problems. After long-term use, sensors may drift or degrade in performance, requiring regular calibration or replacement, increasing the cost and workload of maintenance and management.

[0005] Although temperature sensors have been widely used in many fields and provide important temperature monitoring and control means for all walks of life, there are still some defects and deficiencies in different applications. Therefore, it is necessary to continuously improve and perfect the existing technology to meet the needs of temperature measurement in different fields, improve the accuracy, response speed, sensitivity and stability of sensors, reduce costs, and promote the progress and development of temperature sensor technology. Summary of the invention

[0006] The purpose of the present invention is to provide a temperature sensor with an anisotropic structure, a preparation method and application thereof. The temperature sensor of the present invention can realize the coordinated work of liquid metal deformation and thermal resistance effect under high temperature. Liquid metal has good thermal conductivity and can achieve rapid response to the temperature sensor. In addition, the mechanism of coordinated work of liquid metal deformation and thermal resistance effect can improve the accuracy in high temperature environment, which provides a feasible measure to solve the problems existing in current temperature sensors.

[0007] The present invention is achieved in that:

[0008] First aspect:

[0009] The present invention provides a method for preparing a temperature sensor with an anisotropic structure, comprising the following steps:

[0010] Step 1: Inject liquid metal into the hollow fiber to form a gradient distribution of liquid metal in the channel.

[0011] The liquid metal is a gallium-based alloy, preferably any one or more of gallium metal, gallium-indium alloy, gallium-tin alloy and indium-gallium-tin alloy.

[0012] The injection speed of the liquid metal is 1.0-6.0 mL / min.

[0013] A liquid metal oxide layer is formed between the liquid metal and the inner wall of the anisotropic cavity, and the thickness of the liquid metal oxide layer is 0.1-10 nm, preferably 0.5-5 nm.

[0014] The air inside the cavity structure causes the surface of the injected liquid metal to oxidize to form a liquid metal oxide layer. As the liquid metal is gradually injected, a pressure drop occurs, making it easier for the liquid metal to form a gradient distribution in the microstructure. At the same time, the liquid metal oxide layer also presents a gradient distribution when in contact with the inner wall of the cavity structure.

[0015] The anisotropic capillary channel in the hollow fiber is divided into a front section, a middle section and a rear section; the liquid metal filling rate of the front section is greater than 75%, the liquid metal filling rate of the middle section is 25-75%, and the liquid metal filling rate of the rear section is less than 25%.

[0016] Specifically, as liquid metal is injected into the anisotropic capillary channel, due to the pressure drop, a larger amount of liquid metal enters the microstructure voids in the front region of the capillary channel, and the liquid metal oxide layer is in close contact with the microstructure of the inner wall of the capillary channel; as the liquid metal pressure decreases, the amount of liquid metal entering the microstructure voids in the middle region of the capillary channel is relatively reduced, and the liquid metal oxide layer adheres to the inner wall microstructure in the local area; as the liquid metal pressure further decreases, in the rear region of the capillary channel, the liquid metal oxide layer only adheres to the exposed tip of the microstructure in the capillary channel, and does not penetrate into the gap of the microstructure.

[0017] Step 2: Encapsulation: Use conductive silver paste to seal the two ends of the hollow fiber, and heat and solidify the conductive silver paste. After solidification, a packaged sample is obtained. The purpose of this step of encapsulation is to prevent liquid metal from flowing out from the two ends of the hollow fiber.

[0018] The heating process of the conductive silver paste in this step is: heating the conductive silver paste at 80° C. for 1 hour.

[0019] Step 3: Connect the hollow fiber to the wire through conductive silver paste to lead out the electrode.

[0020] The specific process is to contact the wire with both ends of the hollow fiber through the conductive silver paste (the conductive silver paste in this step is not the conductive silver paste that has been cured in step 2). The conductive silver paste acts as a conductive liquid, and connects the liquid metal in the hollow fiber to the wire during the heating and curing process. The heating process is to heat the conductive silver paste at 80°C for 1 hour.

[0021] Second aspect:

[0022] The present invention also provides a temperature sensor in which thermal resistance effect and deformation work in coordination, and its structure includes: a hollow fiber having an inner wall with a flaky rough structure, liquid metal is injected into the hollow fiber, the liquid metal is distributed in a gradient manner in the hollow fiber, and conductive silver paste is provided at both ends of the hollow fiber, and the conductive silver paste is fixed to the two ends of the hollow fiber by heating and curing. On the one hand, the conductive silver paste is used to seal the two ends of the hollow fiber to prevent the liquid metal from flowing out, and on the other hand, the conductive silver paste acts as a conductor to enable the liquid metal to conduct with the external wire.

[0023] The hollow fiber has a length of 5 to 10 cm and a radial width of 0.04 to 0.2 mm.

[0024] The flaky rough structure attached to the inner wall of the hollow fiber is also called flaky microstructure, and the microstructure scale is 1 to 5 microns.

[0025] The injection speed of the liquid metal is 1.0-6.0 mL / min. The liquid metal is injected into the capillary channel of the hollow fiber. The inner wall of the capillary channel has a microstructure, and the liquid metal forms a gradient distribution state under the action of the microstructure.

[0026] The microstructure is convex, and the liquid metal surface convexes or concave as the temperature increases or decreases.

[0027] The microstructures can also be made larger by adding graphene micro-nanosheets or spheres inside the cavity.

[0028] Liquid metal can more easily form a gradient distribution in the microstructure, which is more conducive to improving the performance of the sensor device. If the flow resistance is small, the distance required to form the gradient segment will be longer, and the more liquid metal there is in the channel, the more unfavorable it is to the sensitivity of the sensor device.

[0029] The liquid metal is any one or more of gallium metal, gallium-indium alloy, gallium-tin alloy and indium-gallium-tin alloy. Gallium-based liquid metal not only performs well in conductivity, but also performs well in mobility. Therefore, the liquid metal is enclosed in a closed solid space containing an air gap, and the liquid metal can move inside the solid and deform in response to external vibrations and pressure changes, thereby causing changes in electrical signals.

[0030] A liquid metal oxide layer is formed between the liquid metal and the inner wall of the cavity, and the thickness of the liquid metal oxide layer is 0.1-10 nm, preferably 0.5-5 nm.

[0031] In the front section of the hollow fiber, the liquid metal filling rate is >75%, in the middle section, the liquid metal filling rate is 25-75%, and in the rear section, the liquid metal filling rate is <25%.

[0032] The third aspect:

[0033] The present invention also provides the use of the temperature sensor obtained by the preparation method described in the first aspect or the temperature sensor described in the second aspect in temperature detection. Further expanding, by detecting the temperature, the distance can also be indirectly measured.

[0034] The present invention has the following beneficial effects:

[0035] 1. Flexible temperature sensors are one of the main research focuses of wearable electronic devices for monitoring human health, and have excellent resolution and deformability. In the present invention, the temperature sensor based on liquid metal is a flexible temperature sensor, which is achieved by precisely controlling the injection speed of liquid metal into the inner wall of a hollow fiber with a rough structure. The liquid metal not only exhibits a thermal resistance effect inside the hollow fiber, but also deforms due to the increase in gas pressure, which is a synergistic effect of liquid metal thermal resistance and strain, thereby enhancing the resolution of the sensor. The temperature sensor provided by the present invention achieves high linearity and a fast response time of 10 seconds in the range of 20°C to 80°C, providing a reliable way to further improve the resolution and response time of the temperature sensor.

[0036] 2. The temperature sensor provided by the present invention has an ingenious structural design, a simple manufacturing process, and has the advantages of low cost, small size, and environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a schematic diagram of the preparation process of the temperature sensor in the present invention.

[0038] Figure 2 is a SEM image of the liquid metal in the hollow fiber in Example 2.

[0039] Figure 3 This is a SEM image of the liquid metal in contact with the inner wall of the hollow fiber in Example 2.

[0040] Figure 4 a, schematic diagram of the sample on a heating plate at 80 °C; b, infrared thermal imaging of the sample during heating on the heating plate; ce, response characteristics of the temperature sensing fiber based on uniform and gradient distribution of liquid metal; f, linearity and variance of the temperature sensing fiber.

[0041] Figure 5 a, schematic diagram of the uniform distribution state of liquid metal; b, schematic diagram of the gradient distribution state of liquid metal; c, schematic diagram of the deformation of liquid metal in the temperature sensor due to heating; df, response characteristics of the temperature sensor under different conditions.

[0042] Figure 6 In the figure, a. temperature sensing is applied to monitor human breathing; b. the temperature sensor is placed in a 70℃ and 20℃ water bath to quickly zero; d. the distance is measured by moving the temperature sensor closer to and further away from the 70℃ water bath environment. DETAILED DESCRIPTION

[0043] Embodiment 1: A temperature sensor with an anisotropic structure.

[0044] The temperature sensor with anisotropic structure provided by the present invention comprises a hollow fiber, in which liquid metal with gradient distribution is formed by injection, and conductive silver paste is arranged at both ends of the hollow fiber.

[0045] The hollow fiber has a length of 5 to 10 cm and a radial width of 0.04 to 0.2 mm. The hollow fiber has an anisotropic capillary channel, and the inner wall of the cavity of the capillary channel is provided with a sheet-like microstructure with a scale of 1 to 5 μm.

[0046] After the liquid metal is injected into the anisotropic capillary channel in the hollow fiber, the capillary channel has a microstructure, and the liquid metal forms a gradient distribution state under the action of the microstructure.

[0047] The liquid metal is distributed in a gradient manner in the hollow fiber. Specifically, starting from the injection port of the liquid metal, the hollow fiber is divided into a front section, a middle section and a rear section in sequence; in the front section, the liquid metal filling rate is >75%; in the middle section, the liquid metal filling rate is 25%-75%; in the rear section, the liquid metal filling rate is <25%.

[0048] The microstructure inside the hollow fiber is convex, and the liquid metal surface inside the hollow fiber is convex or concave as the temperature changes.

[0049] The present invention can also add graphene micro-nano sheets or balls inside the hollow fiber to make the microstructure larger.

[0050] Liquid metal is more likely to form a gradient distribution within the microstructure, which is more conducive to improving the performance of the sensor device. If the flow resistance is small, the distance required to form the gradient segment will be longer, and the more liquid metal there is in the channel, the more unfavorable it is to the sensitivity of the sensor device.

[0051] In the present invention, the liquid metal is a gallium-based alloy, preferably any one or more of gallium metal, gallium-indium alloy, gallium-tin alloy and indium-gallium-tin alloy.

[0052] The injection speed of liquid metal is 1.0-6.0mL / min, at which a gradient distribution can be formed. If the injection speed is less than 1.0mL / min or greater than 6.0mL / min, it is easy to form a uniform distribution. Because the slower the speed, the lower the pressure, the liquid metal is not subjected to enough pressure and cannot be squeezed into the gaps in the microstructure, so its distribution in the hollow fiber is more uniform. If the speed is too high, the liquid metal will be subjected to great pressure from the inlet to the outlet of the hollow fiber, so that it can enter the gaps in the microstructure throughout the entire length, which will also form a more uniform distribution.

[0053] After the liquid metal is injected, a liquid metal oxide layer is formed between the liquid metal and the inner wall of the anisotropic cavity. The thickness of the liquid metal oxide layer is 0.1-10 nm, preferably 0.5-5 nm.

[0054] The air inside the cavity structure causes the surface of the injected liquid metal to oxidize and form a liquid metal oxide layer. As the liquid metal is gradually injected, a pressure drop is generated, making it easier for the liquid metal to form a gradient distribution in the microstructure. At the same time, the liquid metal oxide layer also presents a gradient distribution in contact with the inner wall of the cavity structure. Specifically, as the liquid metal is injected into the anisotropic capillary channel, due to the pressure drop, the amount of liquid metal entering the microstructure voids in the front section of the capillary channel is relatively large, and the liquid metal oxide layer is in close contact with the microstructure of the inner wall of the capillary channel; as the liquid metal pressure decreases, the amount of liquid metal entering the microstructure voids in the middle section of the capillary channel is relatively reduced, and the liquid metal oxide layer adheres to the inner wall microstructure of the local area; as the liquid metal pressure further decreases, in the back section of the capillary channel, the liquid metal oxide layer only adheres to the exposed tip of the microstructure in the capillary channel, and does not penetrate into the gap of the microstructure. In the specific experimental process, the gradient changes in the front and rear areas are small and sometimes negligible, that is, the front and rear areas can be regarded as uniformly distributed. The middle area is the area where the liquid metal gradient changes most significantly. The liquid metal filling rate in the middle area drops from 75% to 25%. The change in this value also shows that it has a large change.

[0055] Gallium-based liquid metals perform well not only in terms of conductivity, but also in terms of mobility. Therefore, the liquid metal is enclosed in a closed solid space containing an air gap, the liquid metal can move inside the solid, and it will deform in response to external vibrations and pressure changes, resulting in changes in electrical signals.

[0056] When the temperature sensor with an anisotropic structure provided by the present invention is used for temperature measurement, especially in the middle area, the liquid metal can flow freely under the action of gas pressure. When the ambient temperature changes, the surface shape of the liquid metal will change under the action of the increased gas pressure, thereby changing the resistance value of the liquid metal inside the hollow fiber. By detecting the change in resistance value, an electrical signal output proportional to the temperature change is obtained, thereby realizing real-time temperature change monitoring.

[0057] Embodiment 2, a method for preparing a temperature sensor with an anisotropic structure.

[0058] Figure 1 The figure is a schematic diagram of the manufacturing process of the temperature sensor. The specific method of preparing the temperature sensor is as follows:

[0059] Step 1: Use a syringe to inject liquid metal into the hollow fiber. The injection rate of the liquid metal is 1.8 mL / min. The liquid metal is distributed in a gradient manner in the hollow fiber. In this embodiment, the liquid metal is specifically an indium gallium tin alloy.

[0060] In order to enhance the stability of the liquid metal in the hollow fiber, PET material fiber with good wettability is used as the hollow fiber. The length of the hollow fiber is 5cm and the radial width is 0.2mm. The liquid metal is distributed in a gradient in the hollow fiber, with the front section being 1cm long, the middle section being 3cm long, and the rear section being 1cm long. The filling rate of the liquid metal in the front section is greater than 75%, and the filling rate of the liquid metal in the middle section gradually decreases from 75% to 25% from front to back; the filling rate of the liquid metal in the rear section is less than 25%. And from Figure 5 As can be seen from b, the front and back parts can be regarded as uniformly distributed, and the middle part is the area with the most significant gradient change.

[0061] Step 2: Encapsulation. Use conductive silver paste to seal both ends of the hollow fiber, and heat and solidify the conductive silver paste. After the solidification is completed, the encapsulated sample is obtained.

[0062] The conductive silver paste heating process is as follows: the conductive silver paste is heated at 80°C for 1 hour.

[0063] Step 3: Connect the hollow fiber to the wire through conductive silver paste to lead out the electrode.

[0064] The specific process is: the conductive wire is connected to the two ends of the hollow fiber through the conductive silver paste. Here, the conductive silver paste is used as a conductive liquid. After heating and curing, the liquid metal is connected to the wire. The heating process is that the conductive silver paste is heated at 80°C for 1 hour. The wire is connected to the measuring instrument to detect the temperature.

[0065] Comparative Example

[0066] The temperature sensor was prepared in the same manner as in Example 2, except that the injection rate of the liquid metal in this comparative example was 8 mL / min, and the liquid metal was evenly distributed in the hollow fiber. The other steps were the same as in Example 2. After the liquid metal was injected into the hollow fiber, the two ends of the hollow fiber were sealed with a conductive silver paste, and the wire was fixed to a glass slide for connection, and then the conductive silver paste was sintered and solidified by heating.

[0067] Figure 2 and Figure 3 This is the distribution state of liquid metal inside the hollow fiber in the sample prepared in Example 2. Figure 2 The SEM images in the figure show the temperature sensing fiber prepared at an injection speed of 1.8 mL / min, revealing numerous microstructures on the inner wall of the fiber ranging from 1 to 4 μm. These microstructures generate capillary forces that prevent the liquid metal from completely adhering to the inner wall of the fiber. In addition, the liquid metal is distributed in a gradient within the hollow fiber, such as Figure 3 shown.

[0068] Figure 4 The figure is a test diagram of the temperature sensor and a signal effect diagram. When used for temperature sensing, heating experiments were conducted on the gradient distribution sensing fiber (the sample in Example 2) and the uniform distribution sensing fiber (the sample in the comparative example). The heating table was used to heat them respectively, and the current signals as the temperature increased were recorded. Figure 4 As shown in a. Figure 4 b shows the surface temperature distribution of the temperature sensing fiber during the heating process on the heating table surface, indicating that the hollow fiber is evenly heated on the heating table surface. In addition, as the heating table gradually reaches 80°C, the current signal of the temperature sensing fiber gradually stabilizes. The research results show that the current signal change rate of the uniformly distributed liquid metal temperature sensing fiber is lower than the change rate of the gradient distributed liquid metal temperature sensing fiber after reaching a stable state. Specifically, Figure 4 As shown in Figure c, the current signal change rate of the uniform distribution fiber is only 3%, while the change rate of the gradient distribution fiber is 5%, indicating that the current signal change rate has increased by 66%. However, the response time also increases accordingly. The time required for the gradient distribution liquid metal temperature sensing fiber to reach a stable state increased by 40 seconds. This is attributed to the existence of additional mechanisms in the gradient distribution liquid metal in addition to the thermal resistance effect. In addition, the corresponding characteristics of the liquid metal uniformly distributed temperature sensing fiber at different temperatures were tested by water bath heating, such as Figure 4d. The experimental results show that as the water bath temperature increases, the current signal of the temperature sensing fiber gradually decreases. In addition, under different water bath temperature conditions, there is no obvious difference in the time required for the temperature sensing fiber to reach a stable state, which is mainly based on the excellent thermal conductivity of the liquid metal itself. However, the temperature sensing fiber with a liquid metal gradient distribution shows a general trend of gradually increasing response time with increasing temperature, especially when the water bath temperature reaches 70°C, the increase in response time is more significant, as shown in Figure 2. Figure 4 In addition, it was observed that there were significant differences between the current signal change rates of the temperature sensing fibers in response to temperature, especially when the water bath temperature reached 70°C, there were obvious differences between the uniformly distributed liquid metal temperature sensing fibers and the gradient distributed liquid metal temperature sensing fibers. Figure 4 f shows the sensitivity and linearity of the temperature sensing fiber to temperature response. As the temperature increases, the slope of the electrical signal change curve of the uniformly distributed liquid metal temperature sensing fiber is -0.052, and the linear variance is 0.985. In contrast, the slope of the electrical signal change curve of the gradient distributed liquid metal temperature sensing fiber is -0.085, and the variance is 0.996. This shows that the gradient distributed liquid metal temperature sensing fiber has higher sensitivity and linearity.

[0069] Figure 5 This is the working principle diagram of the gradient distribution temperature sensor.

[0070] When the liquid metal is evenly distributed in the hollow fiber, the distribution state of the liquid metal in the hollow fiber is shown in the figure Figure 5 In the present invention, an axisymmetric cylindrical tube is used to simulate the geometric shape of the fiber sensor, and a theoretical model can be established from a two-dimensional situation. When the injection port pressure is P0, the pressure inside the fiber changes with the x-axis coordinate:

[0071] P x =P0-xΔP (1)

[0072] The pressure drop per unit length ΔP is described by equation (1). The pressure applied to the liquid metal in the hollow fiber is large enough to completely squeeze it into the groove of the microstructure. The original air volume V0 in the microstructure gap is compressed to V1. At the same time, the adherent oxide scale on the surface of the liquid metal adheres to the side wall of the microstructure, preventing the liquid metal from being squeezed out of the microstructure groove after the injection port pressure disappears. When the injection of liquid metal stops, the additional pressure on the surface of the liquid metal in the microstructure groove can be expressed as:

[0073]

[0074] Among them, r is the radius of the microstructure gap, g is the gravitational acceleration, γ and θ are the surface tension and contact angle of the liquid metal, and h is the wetting height of the liquid metal. At this time, the additional pressure on the liquid metal surface is too large, and the air volume expansion caused by the temperature increase will not have a significant effect on the shape of the liquid metal surface.

[0075] However, when the pressure at the injection port is relatively low, P1, due to the effect of pressure drop, the liquid metal will form an obvious gradient distribution state inside the hollow fiber, as shown in the schematic diagram Figure 5 b. The positions where the gradient starts and ends are marked as x0 and x1 respectively (here the front and rear parts are also considered to be uniformly distributed). At this time, the air pressure and volume at different positions in the temperature sensing fiber can be expressed as:

[0076] P x =P1-xΔP (3)

[0077]

[0078] When the temperature sensing fiber is heated, the volume of the air inside will expand, and the pressure of the gas will increase in a relatively confined space. This can be expressed as:

[0079]

[0080] In this case, the increased gas pressure further changes the curvature of the liquid metal surface, causing the liquid metal to undergo slight deformations, e.g. Figure 5 c. Therefore, it works in synergy with the thermal resistance effect to respond to temperature fluctuations. Figure 5 d-5e shows the response time of the gradient-distributed temperature sensing fiber at different temperatures. Under the condition of 30°C water bath heating, the response time is 5 seconds. When the water bath heating temperature reaches 70°C, the response time increases to 10 seconds. In addition, it is observed that at 70°C, there are obvious differences in the amplitude of the electrical signals between the sensing fibers with different liquid metal distribution states. Therefore, at 70°C, the pressure inside the fiber is sufficient to cause deformation of the liquid metal surface. By continuously heating the temperature sensing fiber in a water bath from 20°C to 70°C and then cooling it at room temperature, the corresponding electrical signal changes are as follows Figure 5 f. A fast response was observed in the range of 20°C to 60°C. However, when reaching 70°C, the response time was delayed, accompanied by a significant increase in the amplitude of the electrical signal change, indicating the influence of liquid metal deformation.

[0081] Figure 6 It is a potential application of temperature sensor. Temperature sensing fiber with gradient distribution can be designed and integrated into the inside of the mask to monitor human health status by monitoring the temperature change of exhaled gas, such as Figure 6In addition, by placing the temperature sensing fiber in a 70℃ and 20℃ water bath environment cyclically, the temperature sensor can be quickly zeroed, as shown in Figure 6 As shown in b-6c, it is shown that the temperature sensor of the present invention has a very fast response speed. By circulating the temperature sensing fiber away from and close to the 70°C water bath environment, the distance can be indirectly measured by detecting the temperature, such as Figure 6 As shown in d.

Claims

1. A temperature sensor having an anisotropic structure, characterized in that: It comprises a hollow fiber with a rough sheet-like structure on the inner wall, in which liquid metal with gradient distribution is formed by injection, and conductive silver paste for sealing the liquid metal is formed at both ends of the hollow fiber by heating and solidification.

2. The temperature sensor with an anisotropic structure according to claim 1, characterized in that the liquid The metal is distributed in a gradient within the hollow fiber. Specifically, starting from the injection port of the liquid metal, the hollow fiber is divided into a front section, a middle section, and a rear section in sequence; in the front section, the liquid metal filling rate is >75%; in the middle section, the liquid metal filling rate is 25%-75%; in the rear section, the liquid metal filling rate is <25%.

3. The temperature sensor with an anisotropic structure according to claim 1, characterized in that: The hollow fiber has a length of 5 to 10 cm and a radial width of 0.04 to 0.2 mm.

4. The temperature sensor with an anisotropic structure according to claim 1, characterized in that the liquid The metal is any one or more of gallium metal, gallium-indium alloy, gallium-tin alloy and indium-gallium-tin alloy.

5. The temperature sensor with an anisotropic structure according to claim 1, characterized in that: The injection speed of the liquid metal is 1.0-6.0 mL / min.

6. A method for preparing a temperature sensor having an anisotropic structure, characterized in that: The steps include: a. Use a syringe to inject liquid metal into the hollow fiber so that the liquid metal is distributed in a gradient manner in the hollow fiber; b. Use conductive silver paste to seal both ends of the hollow fiber, and heat and solidify the conductive silver paste; c. Connect the hollow fiber and the wire together through conductive silver paste.

7. The method for preparing a temperature sensor with an anisotropic structure according to claim 6, characterized in that: The injection speed of the liquid metal in step a is 1.0-6.0 mL / min.

8. The method for preparing a temperature sensor with an anisotropic structure according to claim 7, characterized in that: In step a, the liquid metal is distributed in a gradient in the hollow fiber, specifically: starting from the injection port of the liquid metal, the hollow fiber is divided into a front section, a middle section and a rear section in sequence; in the front section, the liquid metal filling rate is >75%; in the middle section, the liquid metal filling rate is 25%-75%; in the rear section, the liquid metal filling rate is <25%.

9. The method for preparing a temperature sensor with an anisotropic structure according to claim 6, characterized in that: The heating of the conductive silver paste in step b is specifically: heating the conductive silver paste at 80° C. for 1 hour.

10. Use of the temperature sensor with an anisotropic structure according to claim 1 and the temperature sensor with an anisotropic structure prepared according to any one of claims 6 to 9 in temperature detection.